A Soxhlet Extract of Gongronema latifolium Retains Moderate Blood Glucose Lowering Effect and Produces Structural Recovery in the Pancreas of STZ-Induced Diabetic Rats - Al-Hindi, Bassel; Yusoff, Nor A.; Atangwho, Item J.; Ahmad, Mariam; Asmawi, Mohd Z.; Mun, F. Yam (MDPI, 2016)
Gongronema latifolium Benth. (GL) possesses considerable glucose lowering effects able to be utilized on a large-scale. This paper investigates the effects of a Soxhlet extract on hyperglycemia, Langerhans islets and glucose uptake by abdominal muscles. Methods: Ethanol and a Soxhlet apparatus were used to obtain GL ethanolic Soxhlet extract (GLES). It was then administered to randomly-segregated male Sprague-Dawley, normal and STZ-induced diabetic rats, using oral gavage to evaluate blood glucose levels (BGLs), serum lipid profile, insulin levels and the pancreas post-treatment. Results: GLES significantly (p < 0.05) decreased BGLs of normal rats in glucose tolerance testing at a dose of 2 g/kg b.w. but failed to do so in diabetic rats undergoing acute 7-h treatment. Given twice-daily, 1 g/kg b.w. of GLES moderately controlled diabetic BGLs starting from day 10. After 14 days of treatment, 1 g/kg and 0.5 g/kg b.w. of GLES caused 44% and 50% respective increases in the average area of Langerhans islets compared to DC. Using isolated rat abdominal muscle, GLES was found to be a mild insulin-sensitizer. GC-MS analysis revealed the presence of the known glucose-lowering phytosterol, Sitostenone. Conclusion: Despite retaining moderate antidiabetic activity, Soxhlet extraction of Gongronema latifolium probably leads to the destruction of active heat-liable compounds.